Pendekatan Restorative Justice Dalam Menyelesaikan Tindak Pidana Korupsi Di Indonesia Dalam Hal Pemulihan Keuangan Negara - Andi Purnomo (Universitas Sang Bumi Ruwa Jurai, 2023)
In an effort to realize the effectiveness and efficiency of law enforcement in cases of eradicating criminal acts of corruption, the Deputy Attorney General for Special Crimes issued Letter Number: B-1113/F.Fd.1/05/2010 dated 18 May 2010 concerning Priorities and Achievements in Handling Criminal Cases Corruption Crime, which in the letter contains one of the points that instructs every Head of the High Prosecutor's Office in Indonesia so that in cases of suspected criminal acts of corruption, the public's sense of justice will be prioritized, especially for people who, through their awareness, have returned state financial losses (restorative justice), especially in relation to cases Corruption crimes involving relatively small losses to state finances need to be considered not to be followed up. This research uses a normative juridical approach and an empirical juridical approach. The normative juridical approach is carried out by examining library materials or library research. The results of the research explain that the restorative justice approach in criminal acts of corruption as an effort to recover state losses is considered capable of returning state losses and saving state assets. The concept of restorative justice has not been clearly regulated in the justice system in Indonesia, thus placing law enforcers in a difficult and dilemmatic position.